PM / CO2 co-capture porous polyion liquid adsorbent and preparation method thereof

By introducing heterogeneous hydrothermal synthesis technology of imidazolyl and crosslinking agent in ILs, a large pore polyion liquid adsorbent with high specific surface area and stability was prepared, which solved the problem of ILs in the co-capturing process of CO2 and PM. The problems of high viscosity and energy consumption achieve efficient and stable CO2 and PM capture effects.

CN119186526APending Publication Date: 2024-12-27SHENHUA SHENDONG COAL GRP +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411592769.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing ILs face the problems of high viscosity, high energy consumption and low kinetic rate during the co-capturing process of CO2 and PM. Especially when the adsorbent combines with liquid hydrogen sulfide, it increases the difficulty of separation and limits the hydrogen sulfide. Effectiveness and economic feasibility in flue gas purification.

Method used

The initiator containing imidazolyl group is prepared by dissolution diffusion method and the crosslinker are mixed. The integrated porous polyionic liquid adsorbent with high specific surface area and adjustable porosity is prepared by heterogeneous hydrothermal synthesis method to form a three-dimensional hierarchical structure. , enhance the capture capacity of CO2 and PM, and obtain a stable solid adsorbent by freeze-drying.

Benefits of technology

It achieves a wide specific surface area, narrow pore size, polar surface charge and high PM/CO2 capture capacity, and has good mechanical stability and environmental tolerance, simplifies the preparation process and is suitable for complex flue gas environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186526A_ABST
    Figure CN119186526A_ABST
Patent Text Reader

Abstract

The invention provides a PM / CO2 co-capture porous polyion liquid adsorbent and a preparation method thereof, the method comprises the following steps: S1, uniformly dispersing an imidazolyl functional monomer, styrene and an initiator in a reaction solvent to prepare an imidazolyl-containing initiator; s2, mixing the imidazolyl initiator obtained in the step S1 with a cross-linking agent, and placing the mixture in a high-pressure reaction kettle for sol-gel heterogeneous hydrothermal synthesis; and S3, carrying out solvent replacement and freeze drying on the gel obtained in S2 to prepare the monolithic polyion liquid. The prepared porous polyion liquid adsorbent not only has a series of advantages of wide specific surface area, narrow pore size, polar surface charge, PM / CO2 capture capacity and the like, but also has good mechanical stability and environmental tolerance, the preparation process is simple, the condition is mild, and the porous polyion liquid adsorbent is a PM / CO2 co-capture integral adsorbent with wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of integrated synergistic capture solid adsorbents, and in particular to PM / CO 2 Co-capture porous polyionic liquid adsorbent and preparation method thereof. Background Art

[0002] Since the combustion process of fossil fuels is similar to that of operating equipment, carbon dioxide (CO 2 ) and particulate matter (PM) show the same origin in industrial waste gas emissions. The common emission characteristics have prompted countries to turn to collaborative governance to control the greenhouse effect and air pollution. However, factors such as the complexity of chemical reactions in industrial production, the use of specific raw materials, and the volatilization of impurities during smelting have significantly increased the difficulty of collaborative governance in actual scenarios. The combined effect of these factors has given CO 2 The separation of PM and CO poses additional challenges, such as adsorption competition caused by water vapor and corrosive gases. Therefore, it is necessary to consider the complexity of exhaust emissions and focus on overcoming multiple pollutants (CO 2 The challenge of co-capture technology for PM2.5 and PM3.5 is to strike a balance between environmental protection and economic feasibility.

[0003] Ionic liquids (ILs) are salts composed of anions and cations that exist in liquid form at or near room temperature. ILs can precisely modulate Lewis acid-base properties at the molecular level and their unique ionic structure enhances the electrostatic adsorption effect on guest molecules, thus enabling them to capture CO2 dually. 2 and PM. However, in the actual capture process, ILs still face the challenges of high viscosity, high energy consumption and low kinetic rate. In particular, the complex adsorption forces generated when the adsorbent combines with liquid hydrogen sulfide greatly increase the difficulty of separation, thereby limiting the effectiveness and economic feasibility of hydrogen sulfide in flue gas purification. Therefore, it is necessary to explore the structure-activity relationship of ILs and construct a design strategy that combines strong charge characteristics and porosity, so as to achieve a profound optimization of ILs in material design and performance.

[0004] A new type of porous polymer ionic liquids (PILs) has been developed, using ILs as polymer units, usually in gel-like or solid form, to meet the growing demand for improved capture efficiency. By retaining the functionalized ionic properties, porous materials with high specific surface area and adjustable porosity are integrated into PILs, and the intertwining of carbon chains forms a three-dimensional hierarchical porous structure, which provides a new method for CO capture. 2 The co-capture of CO and PM opens up new opportunities for the following reasons: (1) PILs have larger molecular weight, larger specific surface area, and richer pore structure, which is conducive to the synergistic capture of CO 2and PM provide more polar adsorption sites. In contrast, liquid ILs exhibit weaker intermolecular interactions and relatively limited adsorption sites. (2) Molecules with different kinetic diameters can be precisely screened by the hierarchical porous system, thus improving the PILs’ affinity for specific components (CO 2 and PM) separation efficiency, reducing the possibility of impurities competing for adsorption. (3) CO 2 The penetration of PM in micropores forms Knudsen diffusion and follows Fick's law in mesopores / macropores. The design of template-free, self-supporting monolithic PILs based on porous and solid-state properties can better adapt to various exhaust gas treatment equipment and process requirements. Compared with liquid ILs, monolithic PILs exhibit enhanced mechanical properties and can be directly incorporated into the fixed bed adsorption process. Problems such as leakage and splashing of liquids or unstable storage of powders can be avoided by monolithic PILs. Therefore, the development of monolithic PILs can provide a basis for the synergistic capture of CO in complex flue gas environments. 2 and PM to provide more effective, stable and promising solutions. Summary of the invention

[0005] Purpose of the invention: To meet the requirements of synchronous capture of PM and CO in coal mine combustion 2 In order to meet the needs of the present invention, an initiator containing imidazole groups is prepared by a dissolution diffusion method, mixed with a cross-linking agent and synthesized by heterogeneous hydrothermal synthesis to prepare an integral porous polyionic liquid adsorbent with high environmental tolerance and strong charge effect. The adsorbent has not only a wide specific surface area, narrow pore size, polar surface charge, PM / CO 2 It has a series of advantages such as capture capacity, good mechanical stability and environmental tolerance, simple preparation process and mild conditions. It is a PM / CO 2 Co-capture monolithic adsorbent.

[0006] The present invention provides PM / CO 2 A co-capture porous polyionic liquid adsorbent and a preparation method thereof, the method comprising the following steps:

[0007] Step S1, preparing a mixed solution containing an imidazole initiator: dissolving an imidazole functional monomer, styrene and an initiator in a mixed solution consisting of a reaction solvent and deionized water in sequence, and stirring the mixed solution to prepare an imidazole initiator mixed solution;

[0008] Step S2, preparing a polyionic liquid gel: dissolving a crosslinking agent in a mixed solution A composed of a reaction solvent and deionized water, mixing the mixed solution containing an imidazole group initiator with the mixed solution A and placing the mixture in a high-pressure reactor, and using a Friedel-Crafts alkylation reaction to perform a sol-gel heterogeneous hydrothermal synthesis to prepare a polyionic liquid gel;

[0009] Step S3, preparing a monolithic porous polyionic liquid adsorbent: taking out the gel after the reaction is completed and performing solvent replacement, and obtaining a monolithic porous polyionic liquid by freeze drying.

[0010] In step S1, the imidazole functional monomer is at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-methylimidazolium tetrafluoroborate, 1-ethylimidazolium trifluoroacetate, and 1-butyl-3-methylimidazolium saccharinate;

[0011] The initiator is at least one of azobisisobutyronitrile, ferric chloride, zinc dichloride, and trifluoromethanesulfonic acid.

[0012] The reaction solvent is at least one of tetrahydrofuran, dichloromethane, trifluoroacetic acid and toluene.

[0013] In step S1, the molar ratio of the imidazole functional monomer to styrene is 2:1 to 1:2, and the volume ratio of the reaction solvent to deionized water is 5:1 to 15:1.

[0014] In step S2, the cross-linking agent is at least one of N,N'-methylenebisacrylamide, divinylbenzene, boric acid, and polymethyl methacrylate.

[0015] In step S2, the molar ratio of the imidazole functional monomer to the cross-linking agent is 1:1 to 1:3.

[0016] In step S2, the reaction solvent is at least one of tetrahydrofuran, dichloromethane, trifluoroacetic acid, and toluene, and the volume ratio of the reaction solvent to deionized water is 5:1 to 15:1.

[0017] In step S2, the temperature of the Friedel-Crafts alkylation reaction is 55-85° C., and the reaction time is 48-84 hours.

[0018] In step S3, the solvent used for the solvent replacement is at least one of deionized water, tetrahydrofuran, ethanol and methanol.

[0019] In step S3, the freeze-drying temperature is less than or equal to -50°C, the vacuum degree is less than or equal to 100 Pa, the freeze-drying time is 8 to 12 hours, and the diameter of the obtained integral porous polyionic liquid is 5 cm and the height is 6 cm.

[0020] The present invention also provides PM / CO 2 The co-capture porous polyionic liquid adsorbent is prepared by the method described and can be applied to the particulate matter and CO in coal mine combustion. 2 Collaborative capture and separation in an environment where equal mixture components coexist.

[0021] Beneficial effect: The present invention provides a PM / CO 2The invention discloses a co-capture porous polyionic liquid adsorbent and a preparation method thereof. The mixed solution containing an imidazole initiator is prepared by a dissolution diffusion method, mixed with a crosslinking agent and placed in a high-pressure reactor, and a polyionic liquid gel is prepared by a Friedel-Crafts alkylation reaction to undergo a sol-gel heterogeneous hydrothermal synthesis. The gel after the reaction is completed is taken out and the solvent is replaced, and a monolithic porous polyionic liquid is obtained by freeze drying. The specific surface area of ​​the solid adsorbent is 117 to 357 m 2 / g, average pore size is 1.09~2.99nm, PM filtration efficiency is 88.4~97.2%, CO 2 The adsorption capacity is 1.3-2.4 mmol / g, and the air resistance is less than 206 Pa. It not only has a wide specific surface area, narrow pore size, polar surface charge, PM / CO 2 It has a series of advantages such as capture capacity, good mechanical stability and environmental tolerance, simple preparation process and mild conditions. It is a PM / CO 2 Co-capture monolithic adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0023] Figure 1 is a scanning electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 1.

[0024] Figure 2 is a transmission electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 1.

[0025] Figure 3 This is the Fourier transform infrared spectrum of the monolithic porous polyionic liquid adsorbent in Example 1.

[0026] Figure 4 This is the powder X-ray diffraction spectrum of the monolithic porous polyionic liquid adsorbent in Example 1.

[0027] Figure 5 3 is a nitrogen adsorption-desorption isotherm curve of the monolithic porous polyionic liquid adsorbent in Example 1.

[0028] Figure 6 is a scanning electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 2.

[0029] Figure 7 is a transmission electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 2.

[0030] Figure 8This is the Fourier transform infrared spectrum of the monolithic porous polyionic liquid adsorbent in Example 2.

[0031] Fig. 9 This is the powder X-ray diffraction spectrum of the monolithic porous polyionic liquid adsorbent in Example 2.

[0032] Fig.10 This is a nitrogen adsorption-desorption isotherm curve of the monolithic porous polyionic liquid adsorbent in Example 2.

[0033] Fig.11 is a scanning electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 3.

[0034] Fig.12 is a transmission electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 3.

[0035] Fig.13 This is the Fourier transform infrared spectrum of the monolithic porous polyionic liquid adsorbent in Example 3.

[0036] Fig.14 This is the powder X-ray diffraction spectrum of the monolithic porous polyionic liquid adsorbent in Example 3.

[0037] Fig.15 This is a pore size distribution curve of the monolithic porous polyionic liquid adsorbent in Example 3.

[0038] Fig.16 is a scanning electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 4.

[0039] Fig.17 is a transmission electron microscope image of the monolithic porous polyionic liquid adsorbent in Example 4.

[0040] Fig.18 This is the Fourier transform infrared spectrum of the monolithic porous polyionic liquid adsorbent in Example 4.

[0041] Fig.19 This is the powder X-ray diffraction spectrum of the monolithic porous polyionic liquid adsorbent in Example 4.

[0042] Fig. 20 This is a pore size distribution curve of the monolithic porous polyionic liquid adsorbent in Example 4.

[0043] Fig.21 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0044] Example 1

[0045] like Fig.21As shown, this embodiment provides a PM / CO 2 The preparation method of the co-capture porous polyionic liquid adsorbent comprises the following steps:

[0046] S11. Preparation of a mixed solution containing an imidazole initiator: 1-vinyl-3-ethyl imidazole tetrafluoroborate, styrene (molar ratio of 1:1), and an initiator azobisisobutyronitrile were uniformly mixed in a mixed solvent consisting of tetrahydrofuran and deionized water (volume ratio of 10:1), and a mixed solution containing an imidazole initiator was prepared by dissolution diffusion;

[0047] S12. Preparation of polyionic liquid gel: The mixed solution containing imidazole initiator prepared in S11 was fully contacted with the tetrahydrofuran aqueous solution of crosslinking agent N,N'-methylenebisacrylamide (volume ratio of 10:1) and placed in a high-pressure reactor, the reaction temperature was set to 65°C, the reaction time was 72 hours, and the polyionic liquid gel was prepared by sol-gel heterogeneous hydrothermal synthesis using Friedel-Crafts alkylation reaction;

[0048] S13. Preparation of monolithic porous polyionic liquid adsorbent: The polyionic liquid gel prepared in S12 was completely replaced with deionized water as solvent, and freeze-dried (freeze-drying temperature -55°C, vacuum degree 50Pa, freeze-drying time 10 hours) to prepare a monolithic porous polyionic liquid adsorbent with a large specific surface area and polar surface charge, with a specific surface area of ​​357 m 2 / g, and the average pore size is 1.09nm.

[0049] Figure 1 This is a scanning electron microscope image of the monolithic adsorbent obtained in Example 1, which shows that the material has a microscopic morphology composed of agglomeration and accumulation of nanoparticles of different particle sizes.

[0050] Figure 2 This is a transmission electron microscopy image of the monolithic adsorbent obtained in Example 1, showing a dense structure of highly stacked or adhered nanoparticles, and the size of the nanoparticles is 50-200 nm.

[0051] Figure 3 This is the Fourier transform infrared spectrum of the monolithic adsorbent obtained in Example 1, indicating that the material structure has stretching vibrations representing CN, C=N, C=O and characteristic BF.

[0052] Figure 4 The powder X-ray diffraction pattern of the monolithic adsorbent obtained in Example 1 shows that the material has an amorphous nature and the synthesis process involves non-directional and irreversible free radical polymerization.

[0053] Figure 5 This is the nitrogen adsorption-desorption isotherm curve of the monolithic adsorbent obtained in Example 1, indicating that the material has a wide specific surface area.

[0054] In the figure, Transmittance represents transmittance, Wavenumber represents wave number, Intensity represents intensity, 2Theta represents 2θ diffraction angle, Quantity Adsorbed represents adsorption amount, and Relative pressure represents relative pressure.

[0055] Example 2

[0056] This embodiment provides a PM / CO 2 The preparation method of the co-capture porous polyionic liquid adsorbent comprises the following steps:

[0057] S21. Preparation of a mixed solution containing an imidazole initiator: 1-methylimidazole tetrafluoroborate, styrene (molar ratio of 2:1), and an initiator ferric chloride are uniformly mixed in a mixed solvent consisting of dichloromethane and deionized water (volume ratio of 5:1), and a mixed solution containing an imidazole initiator is prepared by dissolution diffusion;

[0058] S22. Preparation of polyionic liquid gel: The mixed solution of the imidazole-containing initiator prepared in S21 was fully contacted with a dichloromethane aqueous solution of divinylbenzene as a crosslinker (volume ratio of 5:1) and placed in a high-pressure reactor, the reaction temperature was set to 55°C, the reaction time was 84 hours, and the polyionic liquid gel was prepared by sol-gel heterogeneous hydrothermal synthesis using Friedel-Crafts alkylation reaction;

[0059] S23. Preparation of monolithic porous polyionic liquid adsorbent: The polyionic liquid gel prepared in S22 was completely replaced with tetrahydrofuran as solvent, and freeze-dried (freeze-drying temperature -50°C, vacuum degree 100Pa, freeze-drying time 12 hours) to prepare a monolithic porous polyionic liquid adsorbent with a large specific surface area and polar surface charge, with a specific surface area of ​​309 m 2 / g, and the average pore size is 1.52nm.

[0060] Figure 6 This is a scanning electron microscope image of the monolithic adsorbent obtained in Example 2, which shows that the material has a microscopic morphology composed of agglomeration and accumulation of nanoparticles of different particle sizes.

[0061] Figure 7 This is a transmission electron microscopy image of the monolithic adsorbent obtained in Example 2, showing a dense structure of highly stacked or adhered nanoparticles, and the size of the nanoparticles is 50-200 nm.

[0062] Figure 8 This is the Fourier transform infrared spectrum of the monolithic adsorbent obtained in Example 2, which shows that the material structure has stretching vibrations representing CN, C=N, C=O and characteristic BF.

[0063] Fig. 9 The powder X-ray diffraction pattern of the monolithic adsorbent obtained in Example 2 shows that the material has an amorphous nature and the synthesis process involves non-directional and irreversible free radical polymerization.

[0064] Fig.10 This is the pore size distribution curve of the monolithic adsorbent obtained in Example 2, indicating that the material has a hierarchical porous structure.

[0065] Example 3

[0066] This embodiment provides a PM / CO 2 The preparation method of the co-capture porous polyionic liquid adsorbent comprises the following steps:

[0067] S31. Preparation of a mixed solution containing an imidazole initiator: 1-ethylimidazole trifluoroacetate, styrene (molar ratio of 3:2), and an initiator zinc dichloride were uniformly mixed in a mixed solvent consisting of trichloroacetic acid and deionized water (volume ratio of 15:1), and a mixed solution containing an imidazole initiator was prepared by dissolution diffusion;

[0068] S32. Preparation of polyionic liquid gel: The mixed solution of the imidazole initiator prepared in S31 was fully contacted with an aqueous solution of trichloroacetic acid of a crosslinking agent boric acid (volume ratio of 15:1) and placed in a high-pressure reactor, the reaction temperature was set to 75 ° C, the reaction time was 60 hours, and the polyionic liquid gel was prepared by sol-gel heterogeneous hydrothermal synthesis using Friedel-Crafts alkylation reaction;

[0069] S33. Preparation of monolithic porous polyionic liquid adsorbent: The polyionic liquid gel prepared in S32 was completely replaced with methanol as solvent, and freeze-dried (freeze-drying temperature -60°C, vacuum degree 20Pa, freeze-drying time 8 hours) to prepare a monolithic porous polyionic liquid adsorbent with a large specific surface area and polar surface charge, with a specific surface area of ​​334 m 2 / g, and the average pore size is 1.61nm.

[0070] Fig.11 This is a scanning electron microscope image of the monolithic adsorbent obtained in Example 3, which shows that the material has a microscopic morphology composed of agglomeration and accumulation of nanoparticles of different particle sizes.

[0071] Fig.12 This is a transmission electron microscopy image of the monolithic adsorbent obtained in Example 3, showing a dense structure of highly stacked or adhered nanoparticles, and the size of the nanoparticles is 50-200 nm.

[0072] Fig.13 This is the Fourier transform infrared spectrum of the monolithic adsorbent obtained in Example 3, indicating that the material structure has stretching vibrations representing CN, C=N, C=O and characteristic BF.

[0073] Fig.14 The powder X-ray diffraction pattern of the monolithic adsorbent obtained in Example 3 shows that the material has an amorphous nature and the synthesis process involves non-directional and irreversible free radical polymerization.

[0074] Fig.15 The nitrogen adsorption-desorption isotherm curve of the monolithic adsorbent obtained in Example 3 shows that the material has a wide specific surface area.

[0075] Example 4

[0076] This embodiment provides a PM / CO 2 The preparation method of the co-capture porous polyionic liquid adsorbent comprises the following steps:

[0077] S41. Preparation of a mixed solution containing an imidazole initiator: 1-butyl-3-methylimidazolium saccharinate, styrene (molar ratio of 1:2), and an initiator trifluoromethanesulfonic acid were uniformly mixed in a mixed solvent consisting of toluene and deionized water (volume ratio of 8:1), and a mixed solution containing an imidazole initiator was prepared by dissolution diffusion;

[0078] S42. Preparation of polyionic liquid gel: The mixed solution of the imidazole-containing initiator prepared in S41 was fully contacted with a toluene aqueous solution of a crosslinking agent polymethyl methacrylate (volume ratio of 8:1) and placed in a high-pressure reactor, the reaction temperature was set to 85°C, the reaction time was 48 hours, and a sol-gel heterogeneous hydrothermal synthesis was performed by Friedel-Crafts alkylation to prepare a polyionic liquid gel;

[0079] S43. Preparation of monolithic porous polyionic liquid adsorbent: The polyionic liquid gel prepared in S42 was completely replaced with ethanol as solvent, and freeze-dried (freeze-drying temperature -55°C, vacuum degree 40Pa, freeze-drying time 10 hours) to prepare a monolithic porous polyionic liquid adsorbent with a large specific surface area and polar surface charge, with a specific surface area of ​​285m 2 / g, and the average pore size is 1.88nm.

[0080] Fig.16 This is a scanning electron microscope image of the monolithic adsorbent obtained in Example 4, which shows that the material has a microscopic morphology composed of agglomeration and accumulation of nanoparticles of different particle sizes.

[0081] Fig.17 This is a transmission electron microscopy image of the monolithic adsorbent obtained in Example 4, showing a dense structure of highly stacked or adhered nanoparticles, and the size of the nanoparticles is 50-200 nm.

[0082] Fig.18This is the Fourier transform infrared spectrum of the monolithic adsorbent obtained in Example 4, which shows that the material structure has stretching vibrations representing CN, C=N, C=O and characteristic BF.

[0083] Fig.19 The powder X-ray diffraction pattern of the monolithic adsorbent obtained in Example 4 shows that the material has an amorphous nature and the synthesis process involves non-directional and irreversible free radical polymerization.

[0084] Fig. 20 This is the pore size distribution curve of the monolithic adsorbent obtained in Example 4, indicating that the material has a hierarchical porous structure.

[0085] Comparative Example 1 (Selecting a pyridine-containing reactive monomer)

[0086] PM / CO was prepared by the method of Example 1. 2 The co-capture porous polyionic liquid adsorbent is different in that in this example, a pyridine-containing reactive monomer is selected to be mixed with a cross-linking agent and an initiator to prepare a monolithic solid adsorbent. Specifically, 1-ethylpyridinium tetrafluoroborate, styrene (molar ratio of 1:1), and initiator azobisisobutyronitrile are uniformly mixed in a mixed solvent consisting of tetrahydrofuran and deionized water (volume ratio of 10:1), and an imidazole-containing initiator mixed solution is prepared by dissolution diffusion; the imidazole-containing initiator mixed solution is fully contacted with a tetrahydrofuran aqueous solution of a crosslinker N,N'-methylenebisacrylamide (volume ratio of 10:1) and placed in a high-pressure reactor, the reaction temperature is set to 65°C, the reaction time is 72 hours, and a Friedel-Crafts alkylation reaction is used to perform a sol-gel heterogeneous hydrothermal synthesis to prepare a polyionic liquid gel; deionized water is used as a solvent for complete replacement, and freeze drying (freeze drying temperature of -55°C, vacuum degree of 50Pa, freeze drying time of 10 hours) is used to prepare an integral porous polyionic liquid adsorbent with a wide specific surface area and polar surface charge, and the specific surface area is 274m 2 / g, and the average pore size is 1.92nm.

[0087] Comparative Example 2 (Preparation of Monolithic Adsorbent Using One-Step Synthesis Method)

[0088] PM / CO was prepared by the method of Example 2. 2Co-capture porous polyionic liquid adsorbent. The difference is that this example uses a one-step method to mix the imidazole-based reaction monomer, crosslinker, initiator and reaction solvent to undergo crosslinking polymerization. Specifically, 1-methylimidazole tetrafluoroborate, styrene (molar ratio of 2:1), initiator ferric chloride, crosslinker divinylbenzene in dichloromethane aqueous solution (volume ratio of 5:1) are fully mixed and placed in a high-pressure reactor, the reaction temperature is set to 55°C, the reaction time is 84 hours, and the Friedel-Crafts alkylation reaction is used to perform sol-gel heterogeneous hydrothermal synthesis to prepare polyionic liquid gel; tetrahydrofuran is used as the solvent for complete replacement, and freeze drying (freeze drying temperature -50°C, vacuum degree 100Pa, freeze drying time 12 hours) is used to prepare an integral porous polyionic liquid adsorbent with a wide specific surface area and polar surface charge, with a specific surface area of ​​259m 2 / g, and the average pore size is 2.18nm.

[0089] Comparative Example 3 (without adding crosslinking agent)

[0090] PM / CO was prepared by the method of Example 3. 2 Co-capture porous polyionic liquid adsorbent. The difference is that no crosslinking agent was added during the synthesis process in this example. Specifically, 1-ethylimidazole trifluoroacetate, styrene (molar ratio of 3:2), and initiator zinc dichloride were uniformly mixed in a mixed solvent composed of trichloroacetic acid and deionized water (volume ratio of 15:1), and an imidazole-containing initiator mixed solution was prepared by dissolution diffusion; the imidazole-containing initiator mixed solution was placed in a high-pressure reactor, the reaction temperature was set to 75°C, the reaction time was 60 hours, and the Friedel-Crafts alkylation reaction was used to perform sol-gel heterogeneous hydrothermal synthesis to prepare polyionic liquid gel; methanol was used as the solvent for complete replacement, and freeze drying (freeze drying temperature -60°C, vacuum degree 20Pa, freeze drying time 8 hours) was used to prepare an integral porous polyionic liquid adsorbent with a wide specific surface area and polar surface charge, with a specific surface area of ​​117m 2 / g, and the average pore size is 2.99nm.

[0091] Structural characterization and performance testing:

[0092] Scanning electron microscope observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics). Figure 1 , Figure 6 , Fig.11 , Fig.16 ).

[0093] Transmission electron microscopy observation: The microstructure of the conjugated microporous polymer-carbon nanotube composite filtration membrane was observed by field emission transmission electron microscopy (model TECNI G2 TF20, FEI Company, the Netherlands). Figure 2 , Figure 7 , Fig.12 , Fig.17 ).

[0094] Functional group structure test: An infrared spectrometer (model VERTEX 70, Bruker, USA) was used to record the functional groups of the conjugated microporous polymer-carbon nanotube composite filter membrane ( Figure 3 , Figure 8 , Fig.13 , Fig.18 ).

[0095] Crystal structure test: An X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) was used to record the crystal structure of the conjugated microporous polymer-carbon nanotube composite filter membrane ( Figure 4 , Fig. 9 , Fig.14 , Fig.19 ).

[0096] Specific surface area test: A gas adsorption instrument (ASAP 2060, Micromeritics, USA) was used to measure the nitrogen adsorption isotherm at 77K ( Figure 5 , Fig.10 , Fig.15 , Fig. 20 ).

[0097] Filtration performance test: The composite membrane (area 25cm 2 ) with a gas flow rate of 1 L / min and cigarettes as the source of particles. Each filter set was tested at least 3 different locations and the results were averaged.

[0098] Carbon dioxide adsorption performance test: A gas adsorption instrument (ASAP 2020, Micromeritics, USA) was used to measure CO 2 Adsorption. High purity gas CO 2 (99.999%) was used for the adsorption measurements, while free space was measured with helium (99.999%). Adsorption isotherms were performed at 273 K (ice-water bath) and 298 K (water bath).

[0099] Experimental results: Figure 1 , Figure 6 , Fig.11 and Fig.16As shown, imidazole-based reaction monomers, initiators, cross-linking agents and reaction solvents are driven by a simple one-pot hydrothermal method to synthesize a self-assembled monolithic imidazole-based polyionic liquid with a porous structure in a homogeneous or heterogeneous phase. In Example 1, the porous polyionic liquid has a microscopic morphology composed of nanoparticles of different particle sizes coagulated and stacked. The spherical stacking can retain the effective specific surface area and open suitable pores, thereby providing adsorption sites and reducing the permeation resistance.

[0100] like Figure 2 , Figure 7 , Fig.12 and Fig.17 As shown, the generated nanoparticles form a compact structure through high stacking or adhesion, and the size of the nanoparticles is 50-200nm. Through the mutual grafting of monomers, the crosslinker forms a stable covalent bridge between the monomers, which promotes the wide distribution of conjugated rings and the enrichment of heteroatoms in the skeleton, giving the imidazole structure variability and diversity, and good macroscopic mechanical flexibility and processability.

[0101] like Figure 3 , Figure 8 , Fig.13 and Fig.18 As shown, at 3137-3125cm -1 The absorption peaks in the range 2386-2281 cm are caused by the stretching vibration of NH -1 The characteristic peak in the range belongs to C=N stretching vibration at 1650cm -1 The center is the stretching vibration of C=O, and the absorption peaks at 1121~1083cm-1 are caused by the stretching vibration of C-N. The appearance of characteristic functional groups indicates the successful in-situ polymerization of conjugated microporous polymers on the carbon nanosurface.

[0102] like Figure 4 , Fig. 9 , Fig.14 and Fig.19 As shown, the diffraction pattern shows a broad and flat characteristic signal peak at 22°, indicating that the synthesis process involves non-directional and irreversible free radical polymerization, resulting in long-range disorder of the porous polyionic liquid and following the kinetically controlled amorphous nature.

[0103] like Figure 5 , Fig.10 , Fig.15 and Fig. 20 As shown in the figure, the adsorption and desorption isotherms all show similar trends, that is, they include a medium-pressure section where the nitrogen adsorption amount gradually increases and a high-pressure section where nitrogen is rapidly adsorbed. Combined with the pore size distribution curve, it shows that the monolithic adsorbent has a hierarchical porous structure. In the figure, Pore Volume represents the pore volume and Pore width represents the pore size.

[0104] Table 1 compares the specific surface area, pore size, PM filtration efficiency, CO 2 Adsorption capacity and air resistance test results. Examples 1-4 and Comparative Examples 1 and 2 have a higher specific surface area (259m 2 / g-357m 2 / g) and a smaller pore size (1.09nm-2.18nm), because the long chains of the carbon skeletons of ionic imidazole or pyridine reaction monomers, initiators and cross-linking agents are intertwined to support a three-dimensional grid-type framework structure, thereby generating permanent pores and providing high internal flux for effective mass transfer; the specific surface area of ​​comparative example 3 is only 117m 2 / g, and the average pore size is 2.99nm. This is because the presence of the cross-linking agent promotes tighter cross-linking and more complete reaction between monomers.

[0105] Table 1

[0106]

[0107]

[0108] PM / CO 2 PM filtration efficiency and CO co-capture of porous polyionic liquid adsorbents 2 Adsorption capacity and air resistance are highly correlated with specific surface area and average pore size. Examples 1-4 and Comparative Examples 1-2 with ideal specific surface area have a high adsorption capacity for PM 0.3 The capture efficiency of CO 2 The adsorption capacity is higher than 1.7mmol / g, and the air resistance is lower than 150Pa, which truly achieves the separation of PM and CO 2 Among them, Example 1 with the highest specific surface area and the smallest pore size performed best in the capture efficiency and adsorption capacity tests. 0.3 The capture efficiency is 97.2%, CO 2 The adsorption capacity is 2.4 mmol / g, which is much higher than that of the comparative example 3 (PM 0.3 The capture efficiency is 88.4%, CO 2 The adsorption capacity is 1.3 mmol / g).

[0109] This shows that the technical solution proposed by the present invention makes the integrated PM / CO 2 The co-capture porous polyionic liquid adsorbent has a wide specific surface area, narrow pore size, polar surface charge, PM / CO 2The advantages of the adsorbent such as high capture capacity and high absorption capacity are likely due to the following: (1) Through the mutual grafting of monomers, the cross-linking agent forms a stable covalent bridge between monomers, which promotes the extensive distribution of conjugated rings and the enrichment of heteroatoms in the skeleton, giving the adsorbent strong structural stability and diversity; (2) The long chains of the carbon skeleton are intertwined to support a three-dimensional grid-like framework structure, thereby generating permanent pores and providing high internal flux for effective mass transfer; (3) The porous skeleton can form variable open active sites, which is conducive to CO 2 and PM, thus achieving dual functionalization of the adsorbent; (4) the presence of strongly electronegative tetrafluoroborate ions in the imidazolyl ionic liquid greatly enhances the dipole property of the adsorbent skeleton, promoting the adsorbent’s absorption of CO 2 and electrostatic adsorption of PM.

[0110] The present invention provides PM / CO 2 There are many methods and approaches to realize the co-capture porous polyionic liquid adsorbent and its preparation method. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be realized by existing technologies.

Claims

1. A method for preparing a porous polyionic liquid adsorbent for PM / CO2 co-capture, characterized in that: The following steps are involved: Step S1, preparing a mixed solution containing an imidazole initiator: dissolving an imidazole functional monomer, styrene and an initiator in a mixed solution consisting of a reaction solvent and deionized water in sequence, and stirring the mixed solution to prepare an imidazole initiator mixed solution; Step S2, preparing a polyionic liquid gel: dissolving a crosslinking agent in a mixed solution A composed of a reaction solvent and deionized water, mixing the mixed solution containing an imidazole group initiator with the mixed solution A and placing the mixture in a high-pressure reactor, and using a Friedel-Crafts alkylation reaction to perform a sol-gel heterogeneous hydrothermal synthesis to prepare a polyionic liquid gel; Step S3, preparing a monolithic porous polyionic liquid adsorbent: taking out the gel after the reaction is completed and performing solvent replacement, and obtaining a monolithic porous polyionic liquid by freeze drying.

2. The method according to claim 1, characterized in that In step S1, the imidazole functional monomer is at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-methylimidazolium tetrafluoroborate, 1-ethylimidazolium trifluoroacetate, and 1-butyl-3-methylimidazolium saccharinate; The initiator is at least one of azobisisobutyronitrile, ferric chloride, zinc dichloride, and trifluoromethanesulfonic acid. The reaction solvent is at least one of tetrahydrofuran, dichloromethane, trifluoroacetic acid and toluene.

3. The method according to claim 2, characterized in that In step S1, the molar ratio of the imidazole functional monomer to styrene is 2:1 to 1:2, and the volume ratio of the reaction solvent to deionized water is 5:1 to 15:

1.

4. The method according to claim 3, characterized in that In step S2, the cross-linking agent is at least one of N,N'-methylenebisacrylamide, divinylbenzene, boric acid, and polymethyl methacrylate.

5. The method according to claim 4, characterized in that In step S2, the molar ratio of the imidazole functional monomer to the cross-linking agent is 1:1 to 1:

3.

6. The method according to claim 5, characterized in that In step S2, the reaction solvent is at least one of tetrahydrofuran, dichloromethane, trifluoroacetic acid, and toluene, and the volume ratio of the reaction solvent to deionized water is 5:1 to 15:

1.

7. The method according to claim 6, characterized in that In step S2, the temperature of the Friedel-Crafts alkylation reaction is 55-85° C., and the reaction time is 48-84 hours.

8. The method according to claim 7, characterized in that In step S3, the solvent used for the solvent replacement is at least one of deionized water, tetrahydrofuran, ethanol and methanol.

9. The method according to claim 8, characterized in that In step S3, the freeze-drying temperature is less than or equal to -50°C, the vacuum degree is less than or equal to 100 Pa, the freeze-drying time is 8 to 12 hours, and the diameter of the obtained integral porous polyionic liquid is 5 cm and the height is 6 cm.

10. PM / CO2 co-capture porous polyionic liquid adsorbent, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Application of amino-functionalized super-crosslinked ionic polymer in adsorption of VOCs (Volatile Organic Compounds)

    CN120094562A